Effects of pyrimidine nucleotides on local cerebral blood flow under conditions of impaired circulation - Milena Khachaturyan; Hakob Topchyan; Arusyak G. Zhamharyan; Lilit T. Soghbatyan; Sona H. Grigoryan; Serob T. Karamyan; Naira H. Adamyan; Knarik M. Shamilyan; Marine G. Balasanyan (Functional Foods in Health and Disease, 2026)
Background: The search for new agents to correct cerebrovascular disorders remains an important task in neuroscience, given the prevalence and increasing incidence of ischemic brain injury and its consequences. In this regard, endogenous biologically active compounds, especially neurochemical components of brain tissue, are of particular interest. Based on these findings, the importance of nucleotides in regulating brain activity has been confirmed. Pyrimidine nucleotides such as cytidine and uridine are essential endogenous compounds that play an important role in nucleic acid synthesis (DNA/RNA), cellular energy transfer, and neuronal membrane phospholipid synthesis, while also acting as signaling molecules. It has been shown that the levels of these compounds decline under ischemic conditions. Cytidine, in the form of cytidine triphosphate (CTP), and uridine, which is first converted to uridine triphosphate (UTP) and then to CTP, contribute to the biosynthesis of phosphatidylcholine and phosphatidylethanolamine in the brain via the Kennedy pathway. Due to their key role in this pathway, the therapeutic potential of cytidine and uridine has been evaluated in neurological disorders such as acute or chronic brain injury and cognitive impairment. Scientific evidence indicates that dietary pyrimidine nucleotides, particularly uridine and its derivatives, exert neuroprotective and neuroregenerative effects, making them promising bioactive compounds for neurofunctional foods and nutraceutical interventions. The combination of uridine and cytidine has been shown to support peripheral nerve regeneration, suggesting a possible role in the regulation of cerebral blood flow. Therefore, the effects of endogenous pyrimidine nucleotides, cytidine and uridine, as well as their combination, were investigated .on cerebral circulation. Objective: To investigate the effects of cytidine-5-monophosphate (CMP), uridine diphosphate (UDP)-choline, and their combination on impaired cerebral circulation caused by brain ischemia. Results: The conducted experiments showed that intraperitoneal injection of CMP at a dose of 10mg/kg after RCCA occlusion did not produce any significant changes in cerebral blood flow compared with the ischemic level. Under conditions of impaired cerebral circulation, UDP-choline administration at a dose of 10mg/kg following RCCA occlusion resulted in an improvement in cerebral blood flow. The result showed that, 60 minutes after occlusion, local cerebral blood flow exceeded the value recorded after occlusion by 35,37 % (p